THE CONCEPT AND MANAGEMENT OF WAJAUL MAFASIL IN UNANI MEDICINE - ZAIDI, ZEHRA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
More than 54 million Americans suffer from some form of arthritis and 23.7 million are limited in their usual activity, primarily due to pain. The study aims to highlight the concept of Arthralgia and the potential of its management in Unani Medicines. Osteoarthritis (OA) is a slowly progressive condition with a variable prognosis. In general, predicting the prognosis in patients with OA is difficult. However, pharmacological therapy can be associated with serious side effects and high costs. Therefore, alternative therapies have been under investigation. Herbal medications have shown the potential for safe and effective management of arthritis. The Unani Medicine is a rich source of classical knowledge on arthritis. OA has been mentioned as Wajaul Mafasil Balghami/Saudawi, and Unani Physicians has been treating this disease successfully with mostly single herbal drugs and their compound formulations for centuries. It has been revealed through animal, in vitro, and clinical studies that most of the single and compound Unani formulations are safe, without any side effects, and effective in OA, especially gout and rheumatoid arthritis. There is a need to conduct studies at Phase III level after analyzing 2nd Phase clinical studies of Unani medicine, so a promising safe, economic, and effective treatment can be provided to the ailing society for OA.